Penyuluhan Pembentukan Peraturan Desa di Desa Labuan, Kecamatan Seram Utara Barat, Kabupaten Maluku Tengah - Makaruku, Alfian Reymon; Wattimury, Eivandro (Penerbit Widina, Widina Media Utama, 2023)
The formation of village regulations is inseparable from the role of the village government and community participation in providing input (aspirations) and participating in village development efforts as well as in the formulation of a village regulation. With this counseling activity, the Labuan Village government and community gained additional knowledge related to the formation of Village Regulations within the scope of Village government. Community participation as a form of participation in improving understanding related to the formation of Village Regulations that have an impact on development. The aim is to increase understanding and legal awareness for the Labuan Village government and its staff and the community. This activity succeeded in increasing legal understanding related to the preparation of village regulations for the village government, BPD, and the community through interactive lecture methods and participatory discussions.ABSTRAKPembentukan peraturan desa tidak terlepas dari peran pemerintah desa dan partisipasi masyarakat dalam memberikan masukan (aspirasi) serta turut serta dalam upaya pembangunan desa maupun dalam perumusan suatu peraturan desa. Dengan adanya kegiatan penyuluhan ini, pemerintah dan masyarakat Desa Labuan memperoleh tambahan pengetahuan terkait dengan pembentukan Peraturan Desa dalam lingkup pemerintahan Desa. Keikutsertaan masyarakat sebagai bentuk partisipasi dalam meningkatkan pemahaman terkait pembentukan Peraturan Desa yang berdampak pada pembangunan. Tujuan meningkatkan pemahaman serta kesadaran hukum bagi pemerintah Desa Labuan dan jajarannya serta masyarakat. Kegiatan ini berhasil meningkatkan pemahaman hukum terkait penyusunan peraturan desa bagi pemerintah desa, BPD, dan masyarakat melalui metode ceramah interaktif dan diskusi partisipatif.